2023
DOI: 10.1021/acsmacrolett.3c00265
|View full text |Cite
|
Sign up to set email alerts
|

UV Irradiation-Induced Cyclic-to-Linear Topological Changes of a Light/pH Dual-Sensitive Cyclic Copolymer for Enhanced Drug Delivery

Abstract: Cyclic polymers with cleavable backbones triggered by either external or internal stimuli can realize simultaneous extracellular stability and intracellular destabilization of cyclic polymer-based nanocarriers but remain seldom reported. To this end, we prepared herein cyclic-ONB-P(OEGMA-st-DMAEMA) (c-ONB-P(OEGMA-st-DMAEMA)) with a light-cleavable junction in the polymer backbone based on oligo (ethylene glycol) monomethyl ether methacrylate (OEGMA) and N,N-dimethylaminoethyl methacrylate (DMAEMA) using a ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…10). 168 These groundbreaking developments underscore the untapped ability and versatility of cyclic polymers in advanced drug delivery technologies, providing opportunities for improved therapeutic strategies in cancer treatment.…”
Section: Biomedical Applications Of Self-assembled Amphiphilic Copoly...mentioning
confidence: 99%
“…10). 168 These groundbreaking developments underscore the untapped ability and versatility of cyclic polymers in advanced drug delivery technologies, providing opportunities for improved therapeutic strategies in cancer treatment.…”
Section: Biomedical Applications Of Self-assembled Amphiphilic Copoly...mentioning
confidence: 99%
“…Among many stimuli-responsive systems, light has been rediscovered as a favourable stimulus due to its convenience and controllability. 2,8–11 Unlike other stimuli, light offers the advantage of being readily accessible and can be employed without additional reagents and under mild reaction conditions. Various light-responsive systems, such as anthracene dimerisation, 12,13 azobenzene, 11,14 and o -nitrobenzyl ( o -NB), 15–18 have been developed, enabling precise control over molecules by adjusting parameters such as light intensity, wavelength, and irradiation time.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that the degradation of hydrogels is mainly dependent on the light cleavage groups on the gel polymer chain segments. One of the most common light-cleavable groups is o -nitrobenzyl ester [ 19 , 20 , 21 , 22 , 23 , 24 ], which can absorb UV light energy and use it for the internal chemical reaction to break the chemical bond. The incorporation of light cleavable groups brings a variety of changes to the properties of hydrogels, yet it also imparts certain complexities to their synthesis.…”
Section: Introductionmentioning
confidence: 99%